Using visualisations to develop skills in astrodynamics. (1st November 2020) - Berthoud, Lucinda; Walsh, Jonathan
ABSTRACT: Learning about the geometry and kinematics of bodies and their trajectories through space (or 'astrodynamics') is challenging due to its three-dimensional nature. To address this, the University of Bristol have developed simulation exercises for students based on a constructivist learning approach and variation learning theory. These exercises use orbit modelling software GMAT to develop skills and address misconceptions. The skills and misconceptions were drawn from the literature and suggested by students. Students were tested with a questionnaire both before and after performing the exercises. A survey at the end of the course provided feedback, which is discussed, along with proposals for further work. Overall, the study shows that 3D visualisation exercises may offer an interesting way to improve conceptual understanding of certain aspects of astrodynamics, particularly for those students struggling with the subject matter.